Periodic solutions of Quasilinear Hyperbolic integro-differential equations of second order - Petrovskii, Ya. B. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We study a periodic boundary-value problem for a quasilinear integro-differential equation with the d’Alembert operator on the left-hand side and a nonlinear integral operator on the right-hand side. We establish conditions under which the uniqueness theorems are true.